WRITING AND READING: A RIGHT FOR EVERYONE! - Nascimento Rodrigues, Kátia (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to present the Writing and Reading Project: a Right for Everyone, developed by me for Escola Municipal Expedicionário Aquino de Araújo. The genesis occurs from concerns and questions as a teacher in the Municipal Networks of Rio de Janeiro (1990 to 1995) and Duque de Caxias (since 1987) in relation to learning to read and write by students and teaching by teachers. Throughout the work, the importance of orality is proposed, for two reasons: it precedes writing and is forgotten at school for the construction of a good text. Speaking and writing as different discursive practices in the same linguistic system. Writing as a point of arrival, as it is carried out in the social sphere. Thus, students are guaranteed the use of their citizenship and taught how to produce texts in the most varied situations. Writing will be given relevance because we live in a literate world where different textual genres circulate. How to teach without the main tool? The text. In this case, the literary text. Another occupation is the path to be taken between the starting point and the arrival point: the student’s difficulty in elaborating, concatenating and articulating ideas to develop or transcribe what is thought. How to coordinate all this? How to understand and produce a text without other skills: listening, speaking and reading? Another relevant point is the teaching of grammar in the text, that is, the teaching of grammatical content through the handling of texts. Is Productive Language Teaching possible, filled with reflective activities, that is, creating epilinguistic analysis activities?